Dificuldades de aprendizagem : influência da Educação Física sob o olhar da psicomotricidade - Brito, Talita Zanon (2020)
As a Physical Education teacher, we realized that students showed difficulties in their physical development, body changes, motor skills, sensory and cognitive capacity due to their constant interaction with the environment, implying in the way children can learn at school. Therefore, this study aimed to analyze Physical Education classes effect, planned from the Psychomotricity perspective, as an auxiliary tool in the teaching-learning process of students with reading and writing difficulties. For the study, 12 children of both sexes, aged between 11 and 12 years old, who attend the 5th and 6th years of regular elementary school, and also the learning articulation room of a State School in the Municipality of Primavera do Leste - MT were considered. The articulation room is an alternative service for students with learning difficulties who attend the regular class and receive a specialized teacher assistance on the shift or in the counter-shift, with appropriate material and pedagogical resources. The research subjects underwent an initial diagnostic evaluation, in which a dictation was made with simple and complex syllable words, before and after the P. E. classes planned from psychomotricity perspective. Eighteen P. E. classes were developed, for a 60 days period and each class lasting one hour. For the data survey, using assumptions of action research with a qualitative approach, and for the data collection process, classes observations were used following a script, recorded in the field diary. In general, it was possible to verify that all children in this study had great motor difficulties. This was to be expected, since studies relating motor development and school performance demonstrate a strong statistical significance between what children are capable of learning (cognitive) and what they are capable of doing (motor). In this research, we can say that children achieved significant advances in their school performance, improving performance in reading and writing through an action plan, with P. E. classes in an action planned and developed jointly with the school's articulation room, under the psychomotricity perspective. This is not intended to say that psychomotricity is a resource for all learning problems, nor to say that inadequate psychomotor development can be the cause of all school difficulties, but we want to leave the proviso through its contribution, which is supported by the evidence of our intervention. An active and well-stimulated child tends to have less school difficulties. Continuity of research is considered opportune, since these results can guide the professionals involved in teaching-learning process to reach the desired success in the schooling process.